Enhancement of conduction noise absorption by hybrid absorbers composed of indium-tin-oxide thin film and magnetic composite sheet on a microstrip line - Kim, Sun-Hong; Kim, Sung-Soo (Applied physics letters, 2014)
In order to develop wide-band noise absorbers with a focused design for low frequency performance, this study investigates hybrid absorbers that are composed of conductive indium-tin-oxide (ITO) thin film and magnetic composite sheets. The ITO films prepared via reactive sputtering exhibit a typical value of electrical resistivity of ≃10−4 Ω m. Rubber composites with flaky Fe-Si-Al particles are used as the magnetic sheet with a high permeability and high permittivity. For the ITO film with a low surface resistance and covered by the magnetic sheet, approximately 90% power absorption can be obtained at 1 GHz, which is significantly higher than that of the original magnetic sheet or ITO film. The high power absorption of the hybrid absorber is attributed to the enhanced ohmic loss of the ITO film through increased electric field strength bounded by the upper magnetic composite sheet. However, for the reverse layering sequence of the ITO film, the electric field experienced by ITO film is very weak due to the electromagnetic shielding by the under layer of magnetic sheet, which does not result in enhanced power absorption.